Effectiveness and safety of follitropin alfa (Ovaleap®) for ovarian stimulation using a GnRH antagonist protocol in real-world clinical practice: a multicenter, prospective, open, non-interventional assisted reproductive technology study - Peter Sydow; Norbert Gmeinwieser; Katrin Pribbernow; Christoph Keck; Inka Wiegratz (BMC, 2020)
Abstract Background The use of recombinant human follicle-stimulating hormone (r-hFSH) in ovarian stimulation protocols for infertility treatment in assisted reproductive technology (ART) clinical practice is well established. More recent advancements include the availability of biosimilar r-hFSH products, which expand the choices available to healthcare practitioners and patients. Better understanding of how such a product contributes to routine clinical practice is valuable to help prescribers make informed treatment choices. The objective of this study was to examine the effectiveness and safety of ovarian stimulation (OS) with follitropin alfa (Ovaleap®) for routine IVF or intracytoplasmic sperm injection treatment in gonadotropin-releasing hormone (GnRH) antagonist cycles in real-world ART clinical practice. Methods This non-interventional, multicenter, prospective study was initiated in 34 specialized reproductive medicine centers in Germany. Eligible women were 18-40 years old with a body mass index < 30 kg/m2, menstrual cycle 24-35 days and anti-Müllerian hormone ≥1 ng/mL, who were undergoing a first OS cycle exclusively with Ovaleap® during routine ART using a GnRH antagonist protocol. Primary effectiveness outcomes were number of retrieved oocytes after OS and clinical pregnancy rate (CPR). Secondary outcomes included fertilization rate, number of transferred embryos, live birth delivery rate, safety, and user satisfaction with the Ovaleap® pen. Result(s) Of 507 women screened, 463 received at least 1 dose of Ovaleap® and 439 had Visit 2 data (per protocol population; PPP). The mean(±SD) number of retrieved oocytes was 11.8 ± 7.2 (PPP). The CPR among women with documented embryo transfer was 41.3% (158/383), resulting in a live birth delivery rate of 31.6% (138/437) among PPP patients with available follow-up information. Overall, 8.6% (40/463) of women reported ≥1 adverse drug reaction. Ovarian hyperstimulation syndrome occurred in 23 (5.0%) patients, rated mild in 14 (3.0%), moderate in 8 (1.7%), and severe in 1 (0.2%). Patients reported high user satisfaction and high convenience with use of the Ovaleap® pen. Conclusion The effectiveness and safety of OS with Ovaleap® in a GnRH antagonist protocol were extended to real-world ART clinical practice for the first time. Trial registration Registered on 22 June 2016 (retrospectively registered) at ClinicalTrials.gov ( NCT02809989 ).